2021
DOI: 10.3389/fpsyt.2021.619367
|View full text |Cite
|
Sign up to set email alerts
|

Core-Symptom-Defined Cortical Gyrification Differences in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a heterogeneous disease that is characterized by abnormalities in social communication and interaction as well as repetitive behaviors and restricted interests. Structural brain imaging has identified significant cortical folding alterations in ASD; however, relatively less known is whether the core symptoms are related to neuroanatomical differences. In this study, we aimed to explore core-symptom-anchored gyrification alterations and their developmental trajectories in ASD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The study discovered that at across time, Fractional Anisotropy (FA) and brain volume of white matter was higher in ASD subjects. Ning et al [36] analyzed the developmental patterns of core-symptom-anchored cortical vertex-wise Gyrification Index (GI) in ASD. They used data from 321 ASD and 350 healthy subjects from ABIDE I, and 14 ASD plus 7 healthy subjects' longitudinal data from the ABIDE II dataset.…”
Section: A Longitudinal Studies On Asd Detectionmentioning
confidence: 99%
“…The study discovered that at across time, Fractional Anisotropy (FA) and brain volume of white matter was higher in ASD subjects. Ning et al [36] analyzed the developmental patterns of core-symptom-anchored cortical vertex-wise Gyrification Index (GI) in ASD. They used data from 321 ASD and 350 healthy subjects from ABIDE I, and 14 ASD plus 7 healthy subjects' longitudinal data from the ABIDE II dataset.…”
Section: A Longitudinal Studies On Asd Detectionmentioning
confidence: 99%
“…For instance, social cognition mainly relies on certain social brain regions, such as the fusiform face area, amygdala, medial prefrontal cortex, anterior cingulate cortex, superior temporal sulcus, and inferior frontal gyrus, RRB has been linked to abnormalities in motor regions, and reduced activation in the right parahippocampal gyrus, cerebellum, left anterior cingulate, and bilateral cingulate in face-processing social tasks has been reported in patients with ASD ( Spencer et al, 2011 ; Patriquin et al, 2016 ; Duret et al, 2018 ; Wilkes and Lewis, 2018 ). In addition, our previous research showed that atypical gyrification patterns encode changes in the symptom dimensions of ASD ( Ning et al, 2021 ). The analysis is complicated by likely distinct symptom clusters or subgroups that exist among patients with ASD ( Lenroot and Yeung, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…After removing brain stem and cerebellum, the cortical thickness was computed by using a projection scheme ( 11 ), which resulted in individual cortical thickness maps. This projection-based thickness estimation is fast and robust, which has been applied in other studies of neuropsychiatric disorders ( 12 , 13 ). The individual maps of cortical thickness cannot be compared because they have a different number of vertexes.…”
Section: Methodsmentioning
confidence: 99%